SOSIALISASI TEMAN BISNIS CATATAN KEUANGAN - Wahyu Nurul Hidayati; Aris Sanulika; Endang Ruhiyat; Holiawati Holiawati; Hari Stiawan (Abdimisi, 2019)
Community service can be interpreted as an academic response from the campus community to the needs, challenges, or problems faced by the community, both directly and indirectly. The general objective of community service activities is to assist fish farmers in the Jampang area, Bogor in overcoming the problems of recording financial statements. The form of activities in the implementation of community service with the theme of financial accounting. The instructors and resource persons involved were Accounting Study Program Lecturers from Pamulang University. The results of the PKM Implementation conducted on 20.21 and 22 September 2019 were adding to their knowledge in the field of accounting, owing to financial records, the ornamental fish group participants in the village of Jampang were very enthusiastic about the material they got from accounting lecturers at the University of Pamulang, participants can directly practice bookkeeping manually, the response of the participants is very good and happy because it is very helpful in learning about financial records. The importance of managing the financial aspects of the business made the farmers' groups aware that income had to be rotated to keep the business going. The suggestion given is that the PKM activities in the future should be encouraged and made as attractive as possible so that they can capture more Ornamental Fish group participants in the village of Jampang, expanding the scope of coverage of the material area can be expanded so that participants can gain more insight. Keywords: Bookkeeping Manual; Entrepreneurship